The Safety of Systemic Treatments That Can Be Used for Geriatric Psoriasis Patients: A Review - Jillian W. Wong; John Y. M. Koo (Dermatology Research and Practice)
Background. Patients with moderate-to-severe psoriasis are often treated with systemic immunosuppressant agents that decrease immune system function. For the elderly, these medications are often problematic due to their already immunosuppressed state and comorbidities. However, there are few studies examining the effects of these medications on the elderly age group. Therefore, there is often discomfort among dermatologists treating elderly patients with psoriasis in utilizing systemic agents, frequently resulting in inadequate treatment. Objective. We review the safety profiles of systemic treatments often used to treat psoriasis and their possible adverse risks to the geriatric population. Methods. We conducted a search of PubMed’s Medline database of articles published from 2000 to 2011, which resulted in 14 articles. Conclusion. Treating geriatric patients with moderate-to-severe psoriasis remains a challenge due to immunosenescence and comorbidities. More studies focusing on psoriasis treatment safety in the geriatric population are needed.